2017
DOI: 10.1002/nau.23202
|View full text |Cite
|
Sign up to set email alerts
|

Urinary incontinence, work, and intention to leave current job: A cross sectional survey of the Australian nursing and midwifery workforce

Abstract: Urinary incontinence, work and intention to leave current job: A cross sectional survey of the Australian nursing and midwifery workforce. Neurourology and Urodynamics 999:1-8. DOI: http://dx.doi.org/10.1002/nau.23202 ABSTRACT Aims: To determine the prevalence and severity of urinary incontinence (UI) in a group of female nurses and midwives, and to examine the relationship between UI, work and intention to leave current job.Methods: An electronic survey 'Fit for the future' was distributed to nurses and midwi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
38
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(42 citation statements)
references
References 24 publications
3
38
1
Order By: Relevance
“…Two‐thirds (61.5%) of nurses in our study reported back pain and almost half (48.7%) experienced urinary incontinence. These prevalence rates are somewhat higher than the state wide survey of Australian nurses and midwives (mean age 48 years) at 46.6% for back pain (Perry et al, ) and 32% for urinary incontinence (Pierce et al, ) despite similar reporting measures and our younger sample (mean age 42.3 years). Our sample characteristics may reflect the urban hospital setting and there may be response bias for reporting of urinary symptoms.…”
Section: Discussioncontrasting
confidence: 59%
See 1 more Smart Citation
“…Two‐thirds (61.5%) of nurses in our study reported back pain and almost half (48.7%) experienced urinary incontinence. These prevalence rates are somewhat higher than the state wide survey of Australian nurses and midwives (mean age 48 years) at 46.6% for back pain (Perry et al, ) and 32% for urinary incontinence (Pierce et al, ) despite similar reporting measures and our younger sample (mean age 42.3 years). Our sample characteristics may reflect the urban hospital setting and there may be response bias for reporting of urinary symptoms.…”
Section: Discussioncontrasting
confidence: 59%
“…However, the finding that nurses with restricted toilet access or delayed voiding practices were more likely to report back pain was unexpected. Common factors may contribute to the development of back pain and LUTS such as urinary incontinence (Pierce, Perry, Gallagher, & Chiarelli, ; Smith, Russell, & Hodges, ). Two‐thirds (61.5%) of nurses in our study reported back pain and almost half (48.7%) experienced urinary incontinence.…”
Section: Discussionmentioning
confidence: 99%
“…The other LUTS subtypes investigated were urinary urgency, increased daytime urinary frequency, nocturia, hesitancy, straining, intermittency, nocturnal enuresis, spraying, feeling of incomplete emptying, slow stream, and bladder pain. Constipation rates ranged from 20.2% to 28.0%, with 4.3% presenting FI and 7.2%, dual incontinence, while only one study reported the prevalence of POP, finding it to be 16.9% in nurses and midwives . Diagnosed sexual dysfunctions were not found, however, these were associated with other PF subtypes …”
Section: Resultsmentioning
confidence: 94%
“…Furthermore, UI was found to be related to restrictions in daily work activities, caused by the fact that the nurses felt wet; smelled of urine; feared losing urine while on duty; tried to resist urinating or because they had to interrupt work frequently to go to the toilet. Two other studies reported that those with “severe or very severe” UI had significantly lower job satisfaction and a greater likelihood of indicating an intention to leave their current job and that occupational stress and psychological strain were higher for those with OAB, especially in relation to nurses …”
Section: Discussionmentioning
confidence: 98%
“…Included studies were all written in English and published between 1990 and 2017. The geographical distribution analysis showed that of the included studies, 8 were conducted in the USA, 3 in Sweden, 1 in Denmark, 1 in UK and 1 in Australia . Most of the studies ( n = 12) were cross‐sectional, 1 was a cohort study, and 1 was a case‐control study …”
Section: Resultsmentioning
confidence: 99%